2014
DOI: 10.1371/journal.pone.0090151
|View full text |Cite
|
Sign up to set email alerts
|

Ambra1 Is an Essential Regulator of Autophagy and Apoptosis in SW620 Cells: Pro-Survival Role of Ambra1

Abstract: Recent research has revealed a role for Ambra1, an autophagy-related gene-related (ATG) protein, in the autophagic pro-survival response, and Ambra1 has been shown to regulate Beclin1 and Beclin1-dependent autophagy in embryonic stem cells. However, whether Ambra1 plays an important role in the autophagy pathway in colorectal cancer cells is unknown. In this study, we hypothesized that Ambra1 is an important regulator of autophagy and apoptosis in CRC cell lines. To test this hypothesis, we confirmed autophagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Ambra1 may primarily play a pro-survival role due to the positive induction of autophagy, which has been previously demonstrated in in vivo (mouse embryos) and in vitro (2FTG cells, SW620 cells and neural stem cells) studies (3,4,73,74). According to these results, the accumulation of Ambra1 in cells will promote autophagy occurrence and suppress apoptosis execution, which may decrease the effectiveness of chemotherapy.…”
Section: Ambra1 In Cell Survival and Implications For Chemotherapy Rementioning
confidence: 58%
See 1 more Smart Citation
“…Ambra1 may primarily play a pro-survival role due to the positive induction of autophagy, which has been previously demonstrated in in vivo (mouse embryos) and in vitro (2FTG cells, SW620 cells and neural stem cells) studies (3,4,73,74). According to these results, the accumulation of Ambra1 in cells will promote autophagy occurrence and suppress apoptosis execution, which may decrease the effectiveness of chemotherapy.…”
Section: Ambra1 In Cell Survival and Implications For Chemotherapy Rementioning
confidence: 58%
“…Although certain studies indicate that autophagy participates in chemotherapy resistance, the mechanism is not yet clear (1). A recent series of studies suggest that activating molecule in Beclin 1-regulated autophagy protein 1 (Ambra1) is an important factor in regards to the association between autophagy and apoptosis, and may control the reciprocal conversion between the two processes to decide the resulting cell death or survival (2)(3)(4). Therefore, Ambra1 may be an important factor of autophagy involved in cancer treatment and chemotherapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first BECN1 region to be directly implicated in up-regulating autophagy in response to starvation, rather than impacting general autophagy levels. Both AMBRA1 and UVRAG have previously been shown to also be important for the up-regulation of autophagy (8, 72, 74). This may suggest that mutation of conserved BECN1 FHD residues abolishes the interaction with either AMBRA1 or UVRAG, or perhaps yet some other uncharacterized interaction, thereby abrogating the starvation-induced up-regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found increased expression of LC3-II and Ambra1 in CRC cell lines after transfection with EZH2-shRNA or addition of exogenous DZNep. LC3-II and Ambra1 are the marker proteins of occurrence of autophagy [30,31,32]. Our previous study evidenced that the increased expression of Ambra1 corresponded to the induction of autophagy [33].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple epigenetic mechanisms, such as chromatin modulation, histone modification, and microRNAs (miRNAs) that regulate the autophagy. For example, the activity of histone deacetylase SIRT1 [32] or histone mark H3K4me [34] regulates autophagy. As an epigenetic gene, EZH2 has only been reported to regulate in HCC cells [35] and glioblastoma multiforme [36].…”
Section: Discussionmentioning
confidence: 99%